SUPPLIER ENGAGEMENT AND TRANSPARENCY IN HALAL PROCUREMENT PRACTICES OF THE HOTEL INDUSTRY - Shari, Sara Shakira; Supian, Kamisah; Md Moid, Muzairihana; Zainal, Mohd Zool Khazani (Jurnal 'Ulwan, 2023)
Halal procurement has not received as much research attention in emerging market contexts as traditional topics like halal traceability and integrity. The practices of halal were found to benefit business performance. With procurement playing a crucial role in organisation performance, it is relevant to integrate halal and procurement to improve the company's performance. This paper empirically examines the influence of supplier engagement and transparency on halal procurement practices in the hotel industry. A quantitative approach was chosen, and a close-ended survey questionnaire was used to collect primary data. A second-generation structural equation method was employed, where SmartPLS 4.0 software was applied to data from 109 hotel establishments in Malaysia. Results show supplier engagement and transparency can help hotel entrepreneurs better comprehend halal procurement practices' intricate role in boosting hotel performance. However, this study was limited to star-rated hotels in parts of Malaysia; therefore, it can be improved by including other industries in the future. This study contributes to hotel practitioners adopting halal procurement in increasing competitiveness and theoretical contribution to developing the study on the halal supply chain.